Supply Chain Model of MSMEs Products in Modern Wholesale Surabaya - Siswati, Endang; Pudjowati, Juliani (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to investigate the supply chain model employed by Micro, Small, and Medium Enterprises (MSMEs) in the retail sector, specifically focusing on the challenges they encounter as suppliers to wholesalers in Surabaya. Through interviews with employees of the Surabaya wholesale centre and MSME actors, this study elucidates the supply chain process, which commences with raw material suppliers and progresses through MSMEs, distribution channels, wholesalers, retailers, and ultimately reaches consumers. A key challenge identified in this research is the difficulty faced by MSMEs in competing with products from large-scale industries within the wholesale centre. Despite these challenges, several MSME products, such as Cakzin sweet and spicy shrimp potato chips and various bread varieties from Sri Roti, have successfully gained a foothold in the Indogrosir Surabaya wholesale centre.